(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2026)
Objective: To report the clinical case of a patient with an ileostomy who underwent Low-Level Laser Therapy (LLLT) for the treatment of peristomal dermatitis. Method: This is a case study conducted in an ostomy care service in southern Brazil in 2025, following the Case Report (CARE) guidelines of the Enhancing the Quality and Transparency of Health Research. Data were collected during 11 outpatient consultations, including clinical assessment of the peristomal lesion, measurement with a ruler, serial photographic records, and analysis of the electronic medical record. Results: A 28-year-old female patient, diagnosed with cervical cancer in 2024, was treated with radiotherapy and brachytherapy. She subsequently developed actinic colitis, rectal stenosis, and a rectovaginal fistula, requiring an ileostomy. The patient presented with peristomal dermatitis, pain, weakness, and difficulty in securing the ostomy appliance. Treatment with LLLT was initiated, resulting in progressive improvement of the skin condition and better adhesion of the ostomy appliance. Throughout follow-up, cutaneous recovery was observed, with reduction of dermatitis and improvement in overall condition. Conclusion: LLLT proved effective in the treatment of peristomal dermatitis in a patient with an ileostomy, promoting rapid skin recovery, improved adhesion of the ostomy appliance, and relief of symptoms. The intervention significantly contributed to the patient’s rehabilitation and quality of life, highlighting its importance as a complementary resource in ostomy care.